Contextualised open educational practices Towards student agency and self-directed learning - Olivier, Jako; du Toit-Brits, Charlene; Bunt, Byron J.; Dhakulkar, Amit (Open textbook library., 2022)
This book covers original research on the implementation of open educational practices through the use of open educational resources at the university level. The emphasis on open education in this book is on contextualising resources, supporting student agency and fostering self-directed learning specifically within a South African milieu. The envisaged chapters cover conceptual and review research and empirical work focussing on open educational practices and the use of renewable assessments. The work starts off with an overview of an institutional-wide open education project that prompted the research followed by research on open education in terms of various modules in the health science, music education, law, philosophy, dietetics, anthropology, French language learning, journalism and political science. There is a clear gap in the literature on open education in terms of open educational practices, specifically in terms of contextualising resources, supporting student agency and fostering self-directed learning in a South African context. Despite the existence of some general works on open education in terms of policy, social justice and open textbooks, this book will be unique in exploring the intersections of openness, specifically with contextualisation, student agency and self-directedness.